Agência humana e estrutura a partir da Teoria da Estruturação - Flavia Galindo (Ciências Sociais Unisinos)
Permanent changes of social life require reflections that address the contextualized individual actions and collective transformative reality. The theory of structuring ponders individual action and the course of collective action, trying to break the socialized sub and hyper prospects of the man. In its conception, ordinary life has a special importance as the vital fabric on social’s life, making it especially important for (re)thinking social praxis with the proposition of new concepts for agency and structure. Thus, we see that the theory of structuring debates the limits and possibilities of the agency as a way of dealing with external phenomena to individuals in the field of human relations. In the Theory of Structure, the agency is linked with three possibilities concerning the structure, systems and structurizing ways, which places it in a contextualized way, showing the possibilities of being operationalized in empirical data.